Mesh generation for underwater acoustic modeling with KRAKEN. (June 2023) - Monteiro, Nuno M.R.; Oliveira, Tiago C.A.
Abstract: Underwater sound modeling is applied in several environmental studies, from assessing underwater noise induced by offshore wind farms to the influence of climate change on ocean temperature. One of the most well-known underwater acoustics models is KRAKEN, an open-source code requiring a mesh to simulate 3D environments. This paper presents OMesh2KRAKEN, a software toolkit that uses OceanMesh2D to generate unstructured meshes for KRAKEN based on realistic environmental data. Two practical study cases in the North Atlantic are presented and discussed. In addition, an idealized 3D shallow water wedge was simulated. Practically, OMesh2KRAKEN can assist in implementing underwater acoustic modeling studies from deep waters to nearshore regions where, for instance, sound propagation maps are required. Indeed, higher mesh resolutions may be required for areas with complex bathymetric features. In these cases, the new tool presents several advantages as it automatically implements different mesh resolutions in areas of interest and prepares the respective environmental files for acoustic computations. Highlights: A new toolkit for underwater acoustic modeling with KRAKEN is introduced. OMesh2KRAKEN uses OceanMesh2D to generate unstructured meshes for KRAKEN. Implementation of different mesh resolutions in areas of interest. Simulation of realistic environmental conditions.